2004
DOI: 10.1111/j.1365-2222.2004.02019.x
|View full text |Cite
|
Sign up to set email alerts
|

Desloratadine in combination with montelukast in the treatment of chronic urticaria: a randomized, double‐blind, placebo‐controlled study

Abstract: The combination of desloratadine plus montelukast is effective in the treatment of CU. It may therefore be a valid alternative in patients with relatively mild CU, in view of its efficacy and the lack of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 28 publications
3
80
0
3
Order By: Relevance
“…This hypothesis is consistent with patient response to other kinds of placebos in randomized trials of urticaria treatments. For example, de Silva and colleagues [27] identified five randomized trials of montelukast in which control patients received oral placebos [30][31][32][33][34]. The changes in symptom severity from baseline to the end of treatment in these studies ranged from a 36% average decrease to a 5% average increase (median = 8% decrease).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is consistent with patient response to other kinds of placebos in randomized trials of urticaria treatments. For example, de Silva and colleagues [27] identified five randomized trials of montelukast in which control patients received oral placebos [30][31][32][33][34]. The changes in symptom severity from baseline to the end of treatment in these studies ranged from a 36% average decrease to a 5% average increase (median = 8% decrease).…”
Section: Discussionmentioning
confidence: 99%
“…14,15,23,[28][29][30] However, in many studies, challenge with ASA 15,19,[22][23][24][25]28,29,31,32 and ⁄ or ASST 13,19,22,[24][25][26][27]31,32 have not been reported or performed. Finally, many patients were affected by physical urticaria.…”
Section: Discussionmentioning
confidence: 99%
“…35 Thus, the results of the controlled studies and clinical experience indicate that these agents are generally safe and well-tolerated, with an incidence of adverse effects generally comparable with placebo. [26][27][28][29][30][31][32][33] Learning points…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study compared the treatment of CIU with desloratadine alone and with desloratadine plus montelukast. According to study data, the combination of desloratadine plus montelukast was found to improve the symptoms and patient quality of life significantly more than desloratadine alone, although it did not have a significant effect on the number of urticarial episodes (57,83,84). Another comparative study of desloratadine alone, montelukast alone and a combination of these two drugs demonstrated desloratadine to be highly effective for the treatment of patients affected by CIU.…”
Section: Leukotriene Receptor Antagonistsmentioning
confidence: 99%